PERAN MODERASI USIA KOGNITIF DALAM KETERKAITAN PERSEPSI NILAI DAN LOYALITAS (STUDI PADA PENGGUNA SMARTPHONE DI ERA PANDEMI COVID-19) - Salman Faris Insani; Ariani Wahyu Wijayanti; Gustita Arnawati Putri (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to explain the relationship between functional values, emotional values, and social values on brand loyalty of smartphone users in the Covid-19 pandemic situation. In addition, this study also attempts to explain the moderating role of cognitive age in relation to the influence of these four variables. The sample in this study were smartphone users in the Solo Raya area who had made repeat purchases for the same brand and were obtained using a non-probability sampling design, through a purposive sampling method. Furthermore, the statistical method used to explain the relationship between the conceptual variables is moderated regression analysis through IBM SPSS Statistic 23 software. The findings in this study indicate that functional values and social values have a significant and positive effect on brand loyalty. However, emotional value has no effect on brand loyalty. Cognitive age is shown to moderate the influence relationship between functional value and emotional value variables on brand loyalty. However, cognitive age is proven not to moderate the influence relationship between social value variables on brand loyalty. The results of this study underline that cognitive age is a variable that plays a role in moderating the influence relationship between perceived value and brand loyalty in the context of smartphone users in the Covid-19 pandemic era. Regarding its role as a moderating variable, the relationship between variables conceptualized in this study can be explained in detail and its significance.